If You Fund Them, Will They Come? Implications From a PhD Fellowship Program on Racial/Ethnic Student Diversity. (September 2021) - Ecton, Walter G.; Bennett, Christopher T.; Nienhusser, H. Kenny; Castillo-Montoya, Milagros; Dougherty, Shaun M.
Prior research demonstrates the important role that financial considerations play in prospective students' decision making when applying to and enrolling in graduate school. Racially/ethnically minoritized students, in particular, face persistent challenges during the graduate application and enrollment process. Capitalizing on a natural experiment, we identify the effects of introducing a PhD fellowship on the composition of applicants and enrolling students in PhD programs at a large public university's graduate school of education. Using administrative data from 9 years of applications, we use difference-in-differences and event study analyses to show that the fellowship increased the number of applicants overall, as well as the share of Black applicants and enrollees in impacted cohorts, with no significant effects on academic preparation. To better understand why and how a PhD fellowship might impact students' application behaviors and experiences once in graduate school, we supplement our primary findings with survey responses from current PhD students at the graduate school of education.